Dentinal microcracks on freshly extracted teeth: the impact of the extraction technique. (7th November 2019) - Arashiro, F. N.; De‐Deus, G.; Belladonna, F. G.; Cavalcante, D. M.; Coelho, M. S.; Silva, E. J. N. L.; Pereira, K. F. S.; da Silva, P. G.; Lopes, R. T.; Souza, E. M.
Abstract: Aim: To evaluate the incidence of root dentinal microcracks after two extraction techniques through micro‐computed tomographic (micro‐CT) analysis. Methodology: Thirty pairs of premolars, extracted for orthodontic reasons, were assigned to two experimental groups, following a split‐mouth design ( n  = 30): traumatic technique group (TTG) – teeth extracted following a conventional protocol using forceps, and an atraumatic technique group (ATG) – teeth extracted following an atraumatic technique protocol in which the root was gently detached from the periodontal ligament using a periotome. All teeth were immediately immersed in distilled water and scanned in a micro‐CT device within 72 h following the extraction. The assessment of the images was completed on cross‐section images by two masked evaluators. The Mann–Whitney test was used to assess the significant differences between the groups regarding the number of cross‐sections displaying microcracks whilst the Fischer's exact test was used to assess differences in the frequency of specimens with defects ( P  < 0.05). Results: A total of 52 750 micro‐CT cross‐sectional images were evaluated. A total of 352 cross‐sections had at least one dentinal defect. Microcracks were observed in five teeth of the TTG group ( n  = 352 slices) and in two teeth of the ATG group ( n  = 103 slices). The statistical analysis used was unable to detect a significant difference between the groups in terms of the number of dentinal microcracks ( P  = 0.233) and in the frequency of teeth displaying microcracks ( P  = 0.424). Conclusion: A small number of sound teeth without endodontic treatment had dentinal microcracks regardless of the extraction technique applied. No difference was noticed between the traumatic and atraumatic techniques in the incidence of microcracks.